Positive affect: phenotypic and etiologic associations with prosocial behaviors and internalizing problems in toddlers - Wang, Manjie; Saudino, Kimberly J. (Frontiers in Psychology, 2015)
Despite evidence for the associations of positive affect to prosocial behaviors and internalizing problems, relatively little is known about the underlying etiology. The sample comprised over 300 twin pairs at age 3. Positive affect, prosocial behaviors, and internalizing problems were assessed using the Toddler Behavior Assessment Questionnaire (Goldsmith, 1996), the Revised Rutter Parent Scale for Preschool Children (Hogg, Rutter, & Richman, 1997), and the Child Behavior Checklist for ages 1.5-5 (Achenbach, 1991), respectively. Positive affect correlated positively with prosocial behaviors, and negatively with internalizing problems. Prosocial behaviors were negatively associated with internalizing problems. The relations of positive affect to prosocial behaviors and internalizing problems were due to environmental effects (shared and nonshared). In contrast, the link between prosocial behaviors and internalizing problems was entirely explained by genetic effects. The current study has moved beyond prior emphasis on negative affect and elucidated the less understood etiology underlying the associations between positive affect, prosocial behaviors, and internalizing problems. This study could guide the development of programs for promoting prosocial behaviors and alleviating internalizing problems in children.